2010
DOI: 10.1007/s11099-010-0068-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term chromium(VI) stress induces different photosynthetic responses in two duckweed species, Lemna gibba L. and Lemna minor L.

Abstract: Physiological responses of two duckweed species, Lemna gibba and Lemna minor, to hexavalent chromium [Cr (VI)] were studied in axenic cultures using short-term (48 h) treatments by K 2 Cr 2 O 7 (0-200 μM). Chlorophyll (Chl) fluorescence parameters and photosynthetic pigment composition of plants were screened to determine the effects of Cr(VI) exposures. The two duckweed species exhibited different sensitivity in the applied Cr(VI) concentration range. Chl fluorescence parameters of dark-adapted and light-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
3
11
1
1
Order By: Relevance
“…However, decrease in the F m in Pb-treated T. triangulare resulted from decrease in the Chl fluorescence intensity when all PSII reaction centers were closed. Similar response reported in Pb-, Hg-, and Cu-treated spinach (Boucher and Carpentier 1999), Cr-treated duckweed (Oláh 2010), and Ni-treated maize (Drążkiewicz and Baszyński 2010).…”
Section: Discussionsupporting
confidence: 80%
“…However, decrease in the F m in Pb-treated T. triangulare resulted from decrease in the Chl fluorescence intensity when all PSII reaction centers were closed. Similar response reported in Pb-, Hg-, and Cu-treated spinach (Boucher and Carpentier 1999), Cr-treated duckweed (Oláh 2010), and Ni-treated maize (Drążkiewicz and Baszyński 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, 0.5 mM Cr(VI) caused an F V / F M decrease comparable with that of 2 mM and much greater that that of 1 and 1.5 mM. This observation is not consistent with our earlier observation concerning the action of a lower Cr(VI) concentration (Augustynowicz et al 2010) as well as the one reported by other investigators (Hörcsik et al 2007; Oláh et al 2010). In the previously mentioned works, direct dependence of Cr(VI) on F V / F M was measured.…”
Section: Discussioncontrasting
confidence: 78%
“…The induction of L. gibba, but not L. minor, antioxidative enzymes at lower Hg, Cd and Cr concentrations suggests a better antioxidative status of L. gibba. Additionally, Oláh et al [43] reported that L. gibba can maintain physiological stability under 48 h of Cr treatment more effectively then L. minor.…”
Section: Discussionmentioning
confidence: 99%